Evaluation of nine microsatellite loci and misidentification paternity frequency in a population of Gyr breed bovines - Curi, Rogerio Abdallah [UNESP]; Lopes, Catalina Romero [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 2002)
Erros de identificação de paternidade são prejudiciais por reduzir o ganho genético anual e comprometer um programa eficiente de melhoramento genético. O objetivo principal deste trabalho foi avaliar o potencial de uso de nove microssatélites em testes de paternidade e investigar a freqüência de erro de identificação de famílias de um rebanho de animais da raça Gir. No experimento foram utilizadas amostras de sangue de quarenta famílias (touro/ vaca/ bezerro) de animais da raça Gir, Puros de Origem e registrados na Associação Brasileira dos Criadores de Zebu (ABCZ). A maior parte dos microssatélites avaliados neste trabalho são recomendados, para Testes de Paternidade em bovinos, pela Sociedade Internacional de Genética Animal (ISAG). As regiões microssatélites TGLA122, TGLA126, BM1824, BMS2533, SPS115, ETH3, ETH10, ETH225 e POTCHA foram amplificadas por meio da técnica de PCR. Os produtos da amplificação foram separados por eletroforese em gel de poliacrilamida desnaturante. A partir dos dados obtidos foram calculadas as freqüências alélicas, diversidade gênica, conteúdo de polimorfismo informativo e probabilidade de exclusão para cada microssatélite. Também foram calculadas as freqüências genotípicas, heterozigosidade, probabilidade de exclusão combinada e probabilidade de Paternidade nas famílias consideradas. A probabilidade de exclusão combinada para todos os microssatélites estudados foi de 0,9789. Os resultados dos testes de paternidade acusaram erro de identificação em onze das 40 famílias estudadas, ou seja, 27,5% da amostra. A probabilidade de paternidade variou entre 0,8691 e 0,9999, com valor médio de 0,9512.

Paternity misidentification is harmful due to the reduction in annual genetic earnings of the population and because it endangers an efficient genetic improvement program. The objectives of the present study was to evaluate nine microsatellites in Paternity Testing and to investigate misidentification paternity frequency in families of Gyr breed bovines population. In the present experiment blood samples from forty Gir breed families ( bull / cow / calf ), registered pure breed in the Zebu Breeders Brazilian Association (ABCZ) were used. The most part of the microsatellites used in this work were recommended by the International Society of Animal Genetics (ISAG). The genomic DNA extraction was performed from whole blood samples. The microsatellites TGLA122, TGLA126, BM1824, BMS2533, SPS115, ETH3, ETH10, ETH225 and POTCHA were amplified by PCR. The amplification products were separated by electrophoresis in denaturing polyacrylamide gel. from the obtained data, allele frequencies, Gene Diversity, Polymorphism Informative Content and Probability of Exclusion for each microsatellite marker were calculated. the genotype frequencies, Heterozygosity, Combined Probability of Exclusion and Probability of Paternity have also been calculated in the considered families. The Combined Exclusion Probability for all microsatellites was around 0.9789. The Paternity Testing results showed misidentification in eleven of the 40 studied families, that means, 27.5% of the sample. The Paternity Probability ranged from 0.8691 to 0.9999, and the mean was 0.9512.
Avaliação de nove locos microssatélite e freqüência de paternidade incorreta em uma população de bovinos da raça Gir
Keywords: DNA; Microssatélites; Paternidade; Bovinos; Gado Gyr; DNA; Microsatellites; Paternity; Bovine; Gyr